Development of Biology Interactive Digital Flipbook on the Subject of Animal Growth and Development - Rifda Abadiyah; Jekti Prihatin; Siti Murdiyah (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2018)
Flipbook is organization of learning materials containing text, sound, animation, and video. This research aimed to produce a learning materials in the form of flipbook, especially on subject of animal’s growth and development for science class grade XII. The flipbook produced should be valid, effective and practical for use in learning process. Flipbook is a 2 dimensional application that is reliable and lightweight. This study used 3 stages from 4 dimensional model which are define, design and develop. The implementation of the developed product was planned by 2 different tests, the first was limited testing and second was field trial. All tests implemented in 44 students of 12 IPA SMA Budi Utomo Sidoarjo. The results showed that 1) an average score of 81.43 gained from 3 different experts which falls into a very valid category, 2) field trial got an average score of 88.46 also falls into very valid category, 3) pre-test, post-test 1 and post-test 2 got normalized gain score at 0.78 which meant that the improvement of learning outcomes after using Flipbook was very high, 4) the effeciency based on the students' response was 97.72% which was interpreted in very good category. It can be concluded that the developed Flipbook was easy and feasible to use in learning. Keywords: Flipbook, validity, effectiveness, practicality result, research and development